2014
DOI: 10.1016/j.still.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Availability and uptake of trace elements in a forage rotation under conservation and plough tillage

Abstract: After 14 years under conventional plough tillage (CT) or conservation minimum tillage (MT), the soil available Al, Fe, Mn, Cu and Zn (0-5, 5-15 and 15-30 cm layers) and their plant uptake were evaluated during two years in a ryegrass-maize forage rotation in NW Spain (temperate-humid region). The three-way ANOVA showed that trace element concentrations in soil were mainly influenced by sampling date, followed by soil depth and tillage system (35-73 %, 7-58 % and 3-11 % of variance explained, respectively). Exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…These results were consistent with Lipiec and Stepniewski (1995) who reported that K and its uptake generally decrease with increasing soil compaction. As Houx et al (2011) these authors did not find differences between tillage systems, but García-Marco et al (2014) showed that soils in plough have more Al than in reduced tillage. In this study, Al was slightly higher in CT and MT with 0.018 g kg 1 than in ST with 0.017 g kg 1 .…”
Section: Nutrients Concentrations In Soilsmentioning
confidence: 93%
See 4 more Smart Citations
“…These results were consistent with Lipiec and Stepniewski (1995) who reported that K and its uptake generally decrease with increasing soil compaction. As Houx et al (2011) these authors did not find differences between tillage systems, but García-Marco et al (2014) showed that soils in plough have more Al than in reduced tillage. In this study, Al was slightly higher in CT and MT with 0.018 g kg 1 than in ST with 0.017 g kg 1 .…”
Section: Nutrients Concentrations In Soilsmentioning
confidence: 93%
“…Rhoton (2000) and García-Marco et al (2014) also concluded that, Fe, Mn and Zn tented to be higher in reduced tillage than in plough tillage under drought year, while opposite was true in the year without water limitation. In this study, Fe could be due to the fact that, during rainfall deficit periods (from May through September), ST and CT improved soil water facilitates and nutrients uptake.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 3 more Smart Citations